Knowledge, attitudes, and practices related to COVID-19 in Indonesia: A post delta variant wave cross-sectional study - Hafidz, Firdaus; Adiwibowo, Insan Rekso; Kusila, Gilbert Renardi; Oktavia, Ayunda; Saut, Benjamin; Jaya, Citra; Siregar, Dedy Revelino; Dhanalvin, Erzan; Tania, Indira; Johana, Johana; Ruby, Mahlil; Baros, Wan Aisyiah (Frontiers in Public Health, 2023)
Introduction: Public information and regulations related to the Coronavirus Disease 2019 (COVID-19) have been widely published and continuously changed. The Indonesian government has responded to the emerging evidence by regularly updating its unprecedented and preventive measures against the transmission of COVID-19 to the public. It is important to understand how the public responded to these updates. This study aims to investigate the knowledge, attitudes, and practices of Indonesians toward COVID-19 after the emergence of the delta variant wave. Methods: A cross-sectional study was conducted among the adult population of non-healthcare workers in Indonesia through an online questionnaire using the SurveyMonkey platform. A total of 1,859 respondents completed this survey from September-October 2021. The knowledge, attitudes, and practices data were analyzed descriptively to find their frequency and percentage. Multivariate analysis was conducted to confirm the factors affecting the respondents’ knowledge, attitudes, and practices with p<0.05 set as significant. Results: Being female, having higher education level, and higher frequency of accessing COVID-19 news showed significant impacts on knowledge, attitudes, and practices (p<0.001). Older age stratification influenced the knowledge level (p<0.05), but had no significant effect on people's attitudes and practices towards COVID-19. Respondents' perceived probability of being exposed to COVID-19 (p<0.05) and their COVID-19 infection frequency (p<0.001) significantly influenced their knowledge. Household income and respondents’ knowledge significantly affected their attitudes towards COVID-19. Furthermore, only their attitudes had a significant impact on the respondents’ practices. Perceived severity, perceived susceptibility, and vaccination status did not significantly influence their knowledge, attitudes, and practices (p>0.05). Conclusion: After more than a year of COVID-19 pandemic, Indonesians maintain their high level of knowledge, attitudes, and practices. COVID-19 disinformation must be combatted through strengthening authorized media, empowering communities, and improving governance among institutions during and post-pandemic.